1997
DOI: 10.1016/s0370-2693(96)01409-8
|View full text |Cite
|
Sign up to set email alerts
|

Excited state Destri-De Vega equation for sine-Gordon and restricted sine-Gordon models

Abstract: We derive a generalization of the Destri -De Vega equation governing the scaling functions of some excited states in the Sine-Gordon theory. In particular configurations with an even number of holes and no strings are analyzed and their UV limits found to match some of the conformal dimensions of the corresponding compactified massless free boson. Quantum group reduction allows to interpret some of our results as scaling functions of excited states of Restricted Sine-Gordon theory, i.e. minimal models perturbe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
246
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(252 citation statements)
references
References 17 publications
5
246
0
1
Order By: Relevance
“…In both cases, we obtained exact agreement between our NLO Lüscher-like formulas and the expansions of the well known NLIEs [41][42][43][44], at least for excitations belonging to the U(1) sectors, in the same way as for the Gross-Neveu model. In the sine-Gordon case we needed to use a generalized version of the identities (4.9):…”
Section: Sine-gordon and O(4) σ-Modelsupporting
confidence: 72%
“…In both cases, we obtained exact agreement between our NLO Lüscher-like formulas and the expansions of the well known NLIEs [41][42][43][44], at least for excitations belonging to the U(1) sectors, in the same way as for the Gross-Neveu model. In the sine-Gordon case we needed to use a generalized version of the identities (4.9):…”
Section: Sine-gordon and O(4) σ-Modelsupporting
confidence: 72%
“…Setting ζ = β 2 /(8π−β 2 ), it can be shown that for ζ = p/(q−p) and α = 1/p, the ground-state energy of the φ 13 perturbation of a general minimal model M p,q is also matched [23,24,[27][28][29]. (Note that this definition of ζ is thus in line with the one given in the introduction.)…”
Section: The Nonlinear Integral Equationmentioning
confidence: 62%
“…The previously-studied sequence (1.1), (1.2) is picked out by the monotonicity of the function c eff as a function of r. In all other cases, somewhat to our surprise, we found that the effective central charge undergoes a number of oscillations as it interpolates between its short and long distance limits. Our approach differs from the TBA method, and is much closer to that of the papers [20][21][22][23][24][25][26], in that a single nonlinear integral equation (NLIE) is proposed to describe infinitely-many different perturbed conformal field theories, each being picked out by an appropriate choice of certain parameters. For massless flows, the one previous example of such an equation was found by Al.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from some exceptional cases (Lee-Yang model, SS-model, Wess-Zumino cosets) both the TBA system and the Y-system are infinite. However, Destri and de Vega noticed [2] that the infinite TBA system for the vacuum of the Sine-Gordon model can be reduced to only one non-linear integral equation, and this was later generalized to excited states [3]. For the models with higher rank groups of symmetries a similar reduction to a few integral equations is usually possible.…”
Section: Introductionmentioning
confidence: 99%